Hungarian Monitoring, 3 October 1990 . [Magyar rádiófigyelő], 1990. október 3 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Celebration of German unity - Soviet-GDR friendship agreement scrapped - Czechoslovak draft law on citizen's rights - Mitterrand's visit to the Persian Gulf - Report on the Gulf crisis - Explosion at the Fogaras chemical works Domestic Affairs: - Jeszenszky's speech at the UN General Assembly meeting - OSCE meeting - Antisemitism in the Hungarian parliament Economy: - Béla Kádár on the tasks of the Hungarian foreign trade - Hungarian-German economic cooperation - Arbitrary apartment occupations - Creation of county-level agricultural offices Külpolitika: - Német egyesülési ünnepség - Szovjet-NDK barátsági szerződés eltörlése - Csehszlovák törvénytervezet az állampolgári jogokról - Mitterrand látogatása a Perzsa-öbölben - Tudósítás az öbölválságról - Robbanás a fogarasi vegyi kombinátban Belpolitika: - Jeszenszky beszéde az ENSZ Közgyűlés ülésén - EBEÉ értekezlet - Antiszemitizmus a magyar parlamentben Gazdaság: - Kádár Béla a magyar külgazdaság feladatairól - Magyar-német gazdasági együttműködés - Önkényes lakásfoglalások - Megyei földművelésügyi hivatalok létrehozása